Beggar thy neighbour or befriend thy neighbour? Asymmetric spillovers of China’s double world-class policy - Jianqin Hang; Xing Ma (PLoS ONE, 2026)
Higher education policies commonly engender certain spillover effects, which frequently remain unaccounted for within the formal policy evaluation framework. Focusing on China’s Double World-Class (DWC) strategy, this paper investigates, from both theoretical and empirical perspectives, whether and how the policy is associated with the research output of non-selected disciplines. Theoretically, this paper puts forward two possible causes of spillovers: reputation enhancement and resource dilution. Based on discipline-level empirical data in Chinese universities from 2014 to 2023 and combined with a panel-regression model, this paper examines whether this policy is associated with changes in the quantity and quality of research outputs among Chinese- and English-language publications across different areas. The results show that the World-Class Discipline (WCD) policy is associated with considerable asymmetric spillover effects on non-selected disciplines. This policy variable is associated with a reduction of 0.62% in the quantity and 1.77% in the quality of research outputs published in Chinese core journals in non-selected disciplines. Meanwhile, it is positively associated with an increase of 5.57% in quantity and 5.06% in quality of research outputs published in English journals. The results of mechanism tests indicate that the enhancement of university reputation and the dilution of educational resources play important roles in the asymmetric spillover effects of WCD policy. The heterogeneity analysis results show that the spillover effects of this policy change across different regions and disciplinary areas. Additionally, this paper integrates the Socialformation Paradigm theory and the Sustainable Social Development theory to further discuss the “delocalization” findings of WCD policy.